2021
DOI: 10.3389/feduc.2021.642686
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Tablets in Norwegian Primary Schools. Examining Outcome Measures in the Second Cohort

Abstract: This study examines the implementation of tablets in primary schools in Norway. The outcome measures in the study are external for the intervention and are recorded data from national tests (National reading, arithmetic and English Tests, Classes 5, 8, and 9, National Mapping Tests for reading and arithmetic, Classes 1–3, and the 2014–2017 National Pupil Survey). The entire study (N = 15, 708) relies on an explanatory, sequential mixed-methods design and in this study we examine the quantitative effects of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
(29 reference statements)
0
6
0
2
Order By: Relevance
“…I begynnaropplaeringa vert det nytta ulike tilnaermingar til bruk av digitale verktøy. Studiar i Norge har undersøkt elevar sine skuleprestasjonar innan lesing, rekning (Krumsvik et al, 2021) og skriving (Spilling et al, 2021) ved bruk av blyant eller nettbrett. Begge studiane viser at val av verktøy i seg sjølv ikkje spelar inn på prestasjonane til elevane.…”
Section: Begynnaropplaering Med Nettbrettunclassified
See 1 more Smart Citation
“…I begynnaropplaeringa vert det nytta ulike tilnaermingar til bruk av digitale verktøy. Studiar i Norge har undersøkt elevar sine skuleprestasjonar innan lesing, rekning (Krumsvik et al, 2021) og skriving (Spilling et al, 2021) ved bruk av blyant eller nettbrett. Begge studiane viser at val av verktøy i seg sjølv ikkje spelar inn på prestasjonane til elevane.…”
Section: Begynnaropplaering Med Nettbrettunclassified
“…I seinare tid er det gjennomført fleire kvantitative forskingsstudiar på bruk av nettbrett i begynnaropplaeringa (t.d. Krumsvik et al, 2021;Spilling et al, 2021), medan kvalitative studiar er etterspurde (Krumsvik et al, 2021). Denne studien vil kartlegge kor mykje og korleis nettbrett er i bruk i eit utval klasser på første trinn.…”
Section: Introduksjonunclassified
“…Recent Norwegian research on the use of iPads has been concerned with whether tablet technology facilitates collaboration (Engen et al, 2017), enhances learning (Kongsgården, 2019;Krumsvik et al, 2018Krumsvik et al, , 2019, contributes to student participation (Kongsgården & Krumsvik, 2016), and how iPads are integrated into teaching and learning processes (Gilje et al, 2020). Two large-scale effect studies on the implementation of iPads in Norwegian primary schools conclude that iPads have rather limited effects on students' learning outcomes (Krumsvik et al, 2018(Krumsvik et al, , 2019. 1 A qualitative case study indicates that the use of tablets in elementary schools leads to distributed knowledge, coherence, and transparency in the students' schoolwork, as well as their high self-confidence in using tablet technology (Kongsgården & Krumsvik, 2016).…”
Section: Perspectives On the Affordances Of Ipadsmentioning
confidence: 99%
“…Tablet technologies have been cited as intuitive, motivating, and supportive of 21st-century skills, which are some of the features that have led to their uptake in schools (Krumsvik et al, 2019). However, there is little research regarding the didactically reasonable inclusion of tablets in schools and review studies have shown the lack of longitudinal research monitoring students' practices with them (Williams & Beam, 2019;Zhang & Nouri, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Brevik (2016) and Niitemaa (2020) revealed that young peoples' language learning (English) in informal learning outside school contexts seemed to have a certain impact on school achievement in English. Krumsvik et al (2021) found that informal learning in English in leisure time can be one of the main factors for the significantly positive results for boys in fifth grade in English (national tests). This seemed to be partly linked to a "spillover effect" from outside school learning where the significantly positive results for boys in fifth grade in English can be interpreted as a sign of the times, when English language immersion in leisure time (e.g.…”
mentioning
confidence: 98%